Is Sudden Sensorineural Hearing Loss an Otologic Emergency? Evidence-Based Cutoff for Optimal Treatment Initiation for Sudden Unilateral Sensorineural Hearing Loss: A Case Series and Meta-Analyses. Issue 3 (14th March 2023) - Klein, Linor; Handzel, Ophir; Shilo, Shahaf; Oron, Yahav; Abu Eta, Rani; Muhanna, Nidal; Ungar, Omer J.
Abstract : Objectives: To study the need for defining unilateral idiopathic sudden sensorineural hearing loss (ISSNHL) as an otologic emergency and establish an evidence-based cutoff for treatment initiation for optimal outcome. Methods: A systematic literature search of "MEDLINE" via "PubMed, " "Embase, " and "Web of Science" and original case series comparing the outcome of steroidal treatment for ISSNHL as a function of delays of patient presentation, of diagnosis, and of treatment initiation. Total delay was defined as days from ISSNHL onset to first steroidal dose and divided into up to 3 days, up to 7 days, up to 14 days, and >14 days. Results: The literature search identified 1, 469 ears and our original case series contributed 154 ears suitable for study inclusion, resulting in 1, 623 ears for statistical analysis. An odds ratio (OR) of 0.42 (95% confidence interval [CI], 0.25–0.71) was calculated for recovery if treatment had been initiated within the third day since the sudden occurrence of a unilateral hearing loss compared with treatment initiation on or after the fourth day (I 2 = 40.1%). The calculated OR for recovery was 0.35 (95% CI, 0.26–0.47) when treatment was initiated during the first 7 days after the sudden hearing loss onset compared with a delay of 8 days or more (I 2 = 52.1%). The OR was 0.31 (95% CI, 0.21–0.46) when treatment was initiated during the first 14 days after the event compared with a longer delay (I 2 = 0.0%). Conclusion: Unilateral ISSNHL should be considered a medical emergency. Initiating treatment before 3 days have elapsed since the event portends the best outcome. Level of Evidence: Level I.